ANALYSIS OF CLOUD TECHNOLOGIES AND INTERACTIONS OF TELECOMMUNICATION SYSTEMS AND NETWORKS - Makhmudova Nargiza Rakhmatullaevna (Scholar Express Journals, 2022)
Telecommunication means the transmission, reception, processing of signals, brands, texts, images, sounds or other types of information using transmissions, radio, optical or other electromagnetic systems." From the Law of the Republic of Uzbekistan "On Telecommunications" Over the past decade, the telecommunications sector has played an important role in ensuring the growth ofproductivity and introducing new technologies. In the future it will be possible to achieve a consistent growth and widespread use of the basic infrastructure in various sectors of the national economy and the various sectors of the Internet, such as e-commerce or the Internet, it is undoubtedly an important phenomenon that embarks on a radical change in the process of evolution
Keywords: Cloud technology; computer; software; model